Measuring management accounting practices using textual analysis - QIU, Fangjuan (Institutional Knowledge at Singapore Management University, 2023)
Management accounting is an important component of managerial decision-making to help guide the overall business strategy in organisations. Appropriate measures of management accounting practices (MAPs) allow academics and practitioners to assess the organisations’ MAP adoption effectively. In this study, based on qualitative information disclosed in annual reports from 2003 to 2019, we construct and validate novel and comprehensive measures of firm-level MAPs using the word embedding model Word2Vec. We illustrate the predictive validity of our measures by examining the determinants and value creation function of fitted MAPs. Our novel measures of MAPs not only provide a solid foundation for large scale sample empirical analyses of management accounting research but also pave a new way to investigate MAPs as a package.